Exploring the potential of impact investing to catalyse transitioning to a circular economy. - Bilewu, Omotayo (Cranfield University, 2023)
There is an overwhelming need to address global social and environmental challenges, alongside an increasing recognition that ‘good business’ is intertwined with ‘doing good’. The emergence of impact investing as an investment vehicle to ‘intentionally’ tackle societal challenges, such as those captured within the United Nations Sustainable Development Goals, alongside generating financial returns is proving attractive to investors and asset managers. This doctoral thesis seeks to provide insights in response to calls for rigorous academic studies towards building institutional legitimacy that should increase market confidence and capital allocation. It starts by investigating the connections between impact investing and the circular economy - two concepts that have generated increased interest in parallel over the last decade. The review reveals that the attributes of impact investing suggest it could play a pivotal role in accelerating the transition to a circular economy. Using a social exchange theory lens, the evolving exchange modalities between investors, intermediaries, and investee companies in the impact investing ecosystem is examined. The results show that a nexus of activities influenced by formal and informal norms govern behaviours and expectations. These norms are crucial in the relational exchange between impact investors, intermediaries and investee companies. A conceptual framework emerges from the study to guide impact investing practice. Furthermore, a single embedded case study is conducted to explore how the exchange partners engage with behaviour change interventions that substitute trust with a mutual opportunity to incorporate sustainable development initiatives in the delivery of an affordable housing development. The findings indicate that mutual goals increase collaboration and cooperation, but are curtailed by the outcome of cost benefit analysis which impinges on trust. Nevertheless, there is scope for impact investors to encourage the uptake of circular economy principles through education and awareness with learning reinforced in project specific facilitated workshop settings.
Keywords: Impact investing; institutional legitimacy; sustainable development goals; circular economy; business-to-business; social exchange theory; impact investing practice